Design of High Performance Miniaturized Lowpass Filter Using New Approach of Modeling - Majidifar, Sohrab (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper a compact microstrip lowpass filter (LPF) is presented using the taper-loaded resonator. Based on a new approach, the resonator response as a function of its model component is obtained. The proposed equation between the insertion loss and LC parameters of the resonator, enable designers to calculate the proper amount of these parameters for a considered response, through the mathematical equations. The response of the final filter is improved using H-shape and spiral-shape defected ground structure. This filter is designed, fabricated and measured and as it is shown in the simulation results, the cutoff frequency is 1.53 GHz, the roll-off rate is better than 29.3 dB/GHz and the insertion loss is less than 0.1 dB from DC to 1.1 GHz.